The Correlation Between Content Schemata and Reading Comprehension on Expository Text of The Second Year Students at MAN 2 Jombang - Noviatul Rochmah; Tutut Wahyuningsih (DIDAKTIKA, 2022)
The English language has four skills that must be mastered. In this case, reading is one of them whether the learner can understand the symbol of printed words or not. On the other hand, if they have a good ability in reading, they will have a better chance to succeed in their study. This research is quantitative, it is focused on the product (the result of the test) not the process of teaching-learning, and the objective is to find out the correlation between students' schemata and their reading comprehension. This correlation is Pearson Correlation because the kind of data correlation is ordinal and interval. The total sample is 83 students, and the significance level is 5% or 0,05 r table for 83 students is 0.213. It is higher than the r table. So, it can be compared that rxy is higher than rtable 0.244 > 0.213. it can be concluded that Ha (Alternative hypothesis) is accepted and H0 is rejected, so the data is Positive correlation. The English teacher should open the class by pre-reading activities to reinforce students' schemata and the students should have good critical thinking to develop their reading comprehension of several types of text, especially narrative text.